2014
DOI: 10.1038/cddis.2014.481
|View full text |Cite
|
Sign up to set email alerts
|

PKCη promotes senescence induced by oxidative stress and chemotherapy

Abstract: Senescence is characterized by permanent cell-cycle arrest despite continued viability and metabolic activity, in conjunction with the secretion of a complex mixture of extracellular proteins and soluble factors known as the senescence-associated secretory phenotype (SASP). Cellular senescence has been shown to prevent the proliferation of potentially tumorigenic cells, and is thus generally considered a tumor suppressive process. However, some SASP components may act as pro-tumorigenic mediators on premaligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 59 publications
7
37
1
Order By: Relevance
“…The increased activity of senescence-associated β-galactosidase (SA-β-gal) is used as a biochemical marker for cellular senescence24. In our study, PRDX3-knockdown cells showed a significantly higher number of SA-β-gal stained cells compared with sh-scr control cells at basal level (Fig.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…The increased activity of senescence-associated β-galactosidase (SA-β-gal) is used as a biochemical marker for cellular senescence24. In our study, PRDX3-knockdown cells showed a significantly higher number of SA-β-gal stained cells compared with sh-scr control cells at basal level (Fig.…”
Section: Resultsmentioning
confidence: 56%
“…Accumulation of oxidative stress and cell-cycle arrest would result in cellular senescence2324. The increased activity of senescence-associated β-galactosidase (SA-β-gal) is used as a biochemical marker for cellular senescence24.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PRKCH , which is hypomethylated in GDM offspring, belongs to the protein kinase C family that is involved in diverse cellular signaling pathways. It can promote cellular senescence through transcriptional upregulation of cell cycle inhibitors p21 and p27 [56]. PRKCH variants have been associated with early-onset obesity [48] and increased stroke risk [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro kinase assays reveal that the mutation enhances the catalytic activity of PKC, as assessed by increased autophosphorylation and substrate phosphorylation (Kubo et al 2007; Zurgil et al 2014). Assuming autoinhibitory constraints are unchanged (as is the case for the activity-enhancing PKCα M489V variant in Alzheimer’s disease), the enhanced catalytic activity would serve as an effective mechanism to allow enhanced activity without compromising the stability of the mutant.…”
Section: Pkc In Degenerative Disease: Gof Mutationsmentioning
confidence: 99%